Roles, Responsibilities and Challenges of Guthi Sansthan (Corporation) for the Conservation of Cultural Heritage in Nepal - Subedi, Salik Ram (KIC International Journal of Social Science and Management, 2022)
Having diverse cost and ethnicity, language and culture, Nepal is rich in cultural heritage. The paper’s main aim is to illustrate the roles and responsibilities of the Guthi Sansthan for the conservation of cultural heritage in Nepal and the challenge it faces. Guthi is an example of a cooperative system. Guthi Sansthan, a government body is more responsible for preserving and managing Nepal’s tangible and intangible cultural heritage. The finding reveals Guthi Sansthan has a leading role in heritage conservation. However, the Guthi still survives and continues as a significant informal heritage conservation system underlining these indigenous systems’ resilience. Many significant heritage places and monuments are now in crisis due to the government policies and encroachment of different organizations and institutions. Therefore, it is essential to recognise the significant value and contribution of Guthi Sansthan for the sustainable heritage conservation and management of cultural heritage by different agencies, including government, policymakers, and practitioners.